Get to Know More About Generation Z - Annisa Kurniati Ana Laila M (Tajdid Al-Athfal, 2023)
Generation Z is a generation that has a different character from the previous generation, namely multitasking, meaning they can do several jobs at one time. Generation Z is also known as the digital generation. Because this generation was born in the rapid development of technology, since childhood, generation Z children have been introduced to technology, if in the past the game was through physical form, this generation Z played through technology media. The more often they play and interact with technology media, the more likely they will be more dependent on technology, this will have negative and positive impacts. These negative and positive impacts will shape the character of children from Generation Z. The purpose of this study is to get to know more about Generation Z, namely the generation born in 1995-2000. This study uses a type of qualitative research with a Library Research approach. Through this research, it can be concluded that Generation Z is a generation that is close to digital technology, so the use of digital space as a teaching tool is important to do.